Students' scientific abilities in the investigative science learning environment (ISLE) approach to static fluid material - Inayatun Diraya; Sentot Kusairi; Hartatiek; Agus Budiyono; Oktavina Pandango (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2026)
Scientific abilities are essential for understanding complex physics concepts such as static fluids. However, these abilities remain low because physics instruction often emphasizes mathematical formulas and provides limited opportunities for investigative activities that connect concepts with empirical phenomena. This study aims to analyze students’ scientific abilities through the Investigative Science Learning Environment (ISLE) approach in static fluid learning and to identify developing indicators of scientific abilities. A mixed methods approach with an embedded experimental design was employed, involving eleventh-grade high school students assigned to an ISLE experimental class and a guided inquiry control class. Data were collected using scientific abilities tests and in-depth interviews. The results show that students in the ISLE class achieved greater improvement than those in the guided inquiry class, with an average N-Gain of 0.73 (high) and an effect size of 3.77 (very large), while the control class obtained an N-Gain of 0.30 (moderate). The highest improvement occurred in problem identification skills, whereas the lowest improvement was found in the ability to formulate testable hypotheses. These findings provide empirical evidence that the ISLE approach effectively enhances students’ scientific abilities and bridges conceptual understanding with investigative practices in physics learning, particularly for static fluid topics.